2022
DOI: 10.1097/wad.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based Eye-tracking Analysis of King-Devick Test Differentiates Persons With Idiopathic Normal Pressure Hydrocephalus From Cognitively Unimpaired

Abstract: Background: Functional defects in eye movements and reduced reading speed in neurodegenerative diseases represent a potential new biomarker to support clinical diagnosis. We investigated whether computer-based eye-tracking (ET) analysis of the King-Devick (KD) test differentiates persons with idiopathic normal pressure hydrocephalus (iNPH) from cognitively unimpaired [control (CO)] and persons with Alzheimer’s disease (AD). Methods: We recruited 68 participants (37 CO, 10 iNPH, and 21 AD) who underwent neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Monitoring potential changes in the performance of eye-movement tests may facilitate the identification of older adults who are at risk of developing AD, becoming a valuable tool for primary health care clinics ( Molitor et al, 2015 ; Holden et al, 2018 ; Wilcockson et al, 2019 ; Pereira et al, 2020 ; Lehtola et al, 2022 ). It has been reported that such recordings could be performed in eye care clinics equipped with cost-effective eye trackers ( Rosen, 2004 ; Dickens and Ramaesh, 2020 ) or at home via devices with built-in cameras such as smartphones or tablets.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring potential changes in the performance of eye-movement tests may facilitate the identification of older adults who are at risk of developing AD, becoming a valuable tool for primary health care clinics ( Molitor et al, 2015 ; Holden et al, 2018 ; Wilcockson et al, 2019 ; Pereira et al, 2020 ; Lehtola et al, 2022 ). It has been reported that such recordings could be performed in eye care clinics equipped with cost-effective eye trackers ( Rosen, 2004 ; Dickens and Ramaesh, 2020 ) or at home via devices with built-in cameras such as smartphones or tablets.…”
Section: Discussionmentioning
confidence: 99%
“…All study participants were clinically examined by a neurologist and participated in a demographic interview. Cognition was evaluated using the Consortium to Establish a Registry for Alzheimer Disease Neuropsychological Test Battery (CERAD-NB), and Clinical Dementia Rating (CDR) 11,12 . The CDR questionnaire includes questions relating to cognition and functional abilities and was used to assess daily function and cognitive decline 13 …”
Section: Methodsmentioning
confidence: 99%
“…Cognition was evaluated using the Consortium to Establish a Registry for Alzheimer Disease Neuropsychological Test Battery (CERAD-NB), and Clinical Dementia Rating (CDR). 11,12 The CDR questionnaire includes questions relating to cognition and functional abilities and was used to assess daily function and cognitive decline. 13 The participants did not exhibit any anamnestic functional or cognitive decline based on the findings of the CERAD-NB, CDR, or demographic interview.…”
Section: Study Design Participants and Protocolmentioning
confidence: 99%